2018
DOI: 10.1016/j.ijhydene.2017.11.111
|View full text |Cite
|
Sign up to set email alerts
|

Highly dense and chemically stable proton conducting electrolyte sintered at 1200 °C

Abstract: The BaCe 0.7 Zr 0.1 Y 0.2-x Zn x O 3- (x = 0.05, 0.10, 0.15, 0.20) has been synthesized by the conventional solid state reaction method for application in protonic solid oxide fuel cell. The phase purity and lattice parameters of the materials have been studied by the room temperature X-ray diffraction (XRD). Scanning electron microscopy (SEM) has been done for check the morphology and grain growth of the samples. The chemical and mechanical stabilities have been done using thermogravimetric analysis (TGA) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…High density and high ionic conductivity are two of the most important criteria for an electrolyte for solid oxide fuel cells. A small percentage of Zn doping at the B-site 37 or adding a sintering additive 38 increases the density and performance of the electrolyte. Zn doping has advantages over Ni for better sintering, crystal structure and density.…”
Section: Resultsmentioning
confidence: 99%
“…High density and high ionic conductivity are two of the most important criteria for an electrolyte for solid oxide fuel cells. A small percentage of Zn doping at the B-site 37 or adding a sintering additive 38 increases the density and performance of the electrolyte. Zn doping has advantages over Ni for better sintering, crystal structure and density.…”
Section: Resultsmentioning
confidence: 99%
“…High density and high ionic conductivity are two of the most important criteria for a good electrolyte. A small percentage of Zn doping at the B-site 37 or adding a sintering additive 38 increases the density and performance of the electrolyte. Zn doping has advantages over Ni for better sintering, crystal structure and density.…”
Section: Rietveld Refinement Of the Neutron Diffraction Data Of The Perovskite-type Ceramic Powdermentioning
confidence: 99%
“…To use a sintering aid, it is crucial that dopant can increase the point defects, and it can also enhance the transportation of ions or electrons to promote sintering. 21,22 Nickel is considered as to be fast diffuser and it enhances the sintering rate of the ceramic powders. It was also reported that during sintering the addition of nickel suppresses the coarsening process of grains to some extent.…”
Section: Introductionmentioning
confidence: 99%